Silver nanoparticles enhanced efficiency of explant surface disinfection and somatic embryogenesis in Begonia tuberous via thin cell layer culture - Tung, Hoang Thanh; Van, Hoang Thi; Bao, Huynh Gia; Bien, Le The; Khai, Hoang Dac; Luan, Vu Quoc; Cuong, Do Manh; Phong, Truong Hoai; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2021)
In vitro culture establishment is one of the most important stages in micropropagation. The disinfectant effectiveness depends on the type of surface disinfectant, concentration and the time treatment. In this initial study, silver nanoparticles (AgNPs) were used as a disinfectant for petioles, flower stalks and stems of Begonia tuberous. In addition, thin cell layer culture (TCL) technique has been applied for the purpose of somatic embryogenesis. The results showed that AgNPs were effective in eliminating infectious microorganisms on B. tuberous explants; which were identified included 4 species of fungi (Fusarium sp., Aspergillus aculeatus, Trichoderma sp. and Penicillium sp.) and 1 species of bacteria (Pseudomonas sp.). At concentrations of 200 ppm and 300 ppm, AgNPs were not only effective in disinfection but also increased the induction rate of somatic embryogenesis in flower stalk TCL explants (approximately 40.00%); a similar effect was observed in stem TCL explants at the same concentration. Meanwhile, for petiole TCL explants, the induction rate of somatic embryogenesis was optimal when using AgNPs at a concentration of 100 - 300 ppm to disinfected the explant. In contrast, at high (400 ppm) or low (50 ppm) concentrations of AgNPs did not play a disinfecting role and stimulated somatic embryogenesis. In addition, explants derived from AgNPs sterilization did not show any abnormalities in somatic embryogenesis with shapes such as globular, heart, torpedo, and cotyledon. AgNPs showed double efficacy in sterilization of explants and improved efficiency of somatic embryogenesis from TCL petioles, flower stalks and stems explants; thus increasing the efficiency micropropagation of B. tuberous.